1992
DOI: 10.1063/1.461979
|View full text |Cite
|
Sign up to set email alerts
|

Photodissociation of molecular chlorine in xenon matrices

Abstract: The photodissociation of Cl2 in crystalline Xe is examined using synchrotron radiation for all state of Cl2 from the C 1Π1u state to the region of Xe exciton absorption. Isolation of atomic chlorine in two dominant trapping sites is observed following photodissociation throughout the spectral region studied. The production efficiency of the thermally stable trapping site was found to increase significantly with temperature and was most pronounced in the region of the onset of the Xe2Cl excitation feature. Corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…15 and 16͒ and Cl 2 ͑Refs. 17-19͒, together with experimental studies of these systems [19][20][21][22][23][24][25][26][27] have demonstrated both caging and mobility of photoproducts. The dynamics of halogens in rare gas solids at high kinetic energies are sensitive to the nonadiabatic processes involving curve crossings between valence, Rydberg, and charge transfer states, and the interaction of the matrix host with these states.…”
Section: Introductionmentioning
confidence: 99%
“…15 and 16͒ and Cl 2 ͑Refs. 17-19͒, together with experimental studies of these systems [19][20][21][22][23][24][25][26][27] have demonstrated both caging and mobility of photoproducts. The dynamics of halogens in rare gas solids at high kinetic energies are sensitive to the nonadiabatic processes involving curve crossings between valence, Rydberg, and charge transfer states, and the interaction of the matrix host with these states.…”
Section: Introductionmentioning
confidence: 99%
“…From the work of McCaffrey et al 10 in a Xe matrix it has been shown that this charge transfer state can be reached with photon wavelengths ranging from 190 up to 160 nm.…”
Section: Communications Femtosecond Study Of Xe-cl 2 Reactions In Clumentioning
confidence: 99%
“…[12][13][14][15][16][17] The entrance channel to the XeϩCl 2 LAR is unique from other laser-induced reactions between Xe and Cl 2 in that it involves a coherent two-photon excitation of the transient Xe-Cl 2 collision pair ͑or bound vdW complex͒ to the ͕Xe ϩ Cl 2 Ϫ ͖ CTS,…”
Section: Introductionmentioning
confidence: 99%